A silk purse from a sow's ear — bioinspired materials based on α-helical coiled coils. (February 2015) - Quinlan, Roy A; Bromley, Elizabeth H; Pohl, Ehmke
Graphical abstract: The micrograph shows GFAP intermediate (10nm) sized filaments negatively stained with uranyl acetate and imaged using a transmission electron microscope. The areas of current and future application for coiled coil assemblies, either as filaments, or as cages, or as synthetic nanocomposite (eg with graphene) are either described or illustrated. Highlights: From wool α-keratins to emergent coiled coil technologies as vaccine platforms. Drug delivery and future nanocomposites. Packing, weaving and storing α-helical coiled coil fibres. Structural tools to design and deliver coiled coil geometries. Abstract : This past few years have heralded remarkable times for intermediate filaments with new revelations of their structural properties that has included the first crystallographic-based model of vimentin to build on the experimental data of intra-filament interactions determined by chemical cross-linking. Now with these and other advances on their assembly, their biomechanical and their cell biological properties outlined in this review, the exploitation of the biomechanical and structural properties of intermediate filaments, their nanocomposites and biomimetic derivatives in the biomedical and private sectors has started.